Proceso de atención de enfermería en adulto con tuberculosis pulmonar en el Hospital General Martin Icaza de la Ciudad De Babahoyo. - Gaibor Vera, Diana Elizabeth (2018)
Pulmonary tuberculosis is a problem for public health at the national level despite the treatments that currently exist and the control measures promoted by the Ministry of Public Health, that when the disease is detected in time, the treatment will give us a favorable result for the patient and his prompt recovery if he follows in a disciplined way the directly observed treatment and the protocol norms indicated according to the scheme corresponding to his pathology. The objective is to apply the process of nursing care in a 53-year-old patient with pulmonary tuberculosis hospitalized in the clinical area in the "San José" room of the Martin Icaza General Hospital in the city of Babahoyo in the second semester of 2017. The process of nursing care necessary for the patient was used, according to his pathology, since it is the basic and essential tool, which scientifically applies the necessary interventions to reduce the risks produced by his illness. In the development of the nursing care process, we were able to know and adapt to the realization of this necessary and timely tool, which serves us in our working life as a future Bachelor of Nursing.